Saturation in Phosphene Size with Increasing Current Levels Delivered to Human Visual Cortex - Bosking, William H.; Sun, Ping; Ozker, Muge; Pei, Xiaomei; Foster, Brett L.; Beauchamp, Michael S.; Yoshor, Daniel (The Journal of neuroscience, 2017)
Electrically stimulating early visual cortex results in a visual percept known as a phosphene. Although phosphenes can be evoked by a wide range of electrode sizes and current amplitudes, they are invariably described as small. To better understand this observation, we electrically stimulated 93 electrodes implanted in the visual cortex of 13 human subjects who reported phosphene size while stimulation current was varied. Phosphene size increased as the stimulation current was initially raised above threshold, but then rapidly reached saturation. Phosphene size also depended on the location of the stimulated site, with size increasing with distance from the foveal representation. We developed a model relating phosphene size to the amount of activated cortex and its location within the retinotopic map. First, a sigmoidal curve was used to predict the amount of activated cortex at a given current. Second, the amount of active cortex was converted to degrees of visual angle by multiplying by the inverse cortical magnification factor for that retinotopic location. This simple model accurately predicted phosphene size for a broad range of stimulation currents and cortical locations. The unexpected saturation in phosphene sizes suggests that the functional architecture of cerebral cortex may impose fundamental restrictions on the spread of artificially evoked activity and this may be an important consideration in the design of cortical prosthetic devices. Understanding the neural basis for phosphenes, the visual percepts created by electrical stimulation of visual cortex, is fundamental to the development of a visual cortical prosthetic. Our experiments in human subjects implanted with electrodes over visual cortex show that it is the activity of a large population of cells spread out across several millimeters of tissue that supports the perception of a phosphene. In addition, we describe an important feature of the production of phosphenes by electrical stimulation: phosphene size saturates at a relatively low current level. This finding implies that, with current methods, visual prosthetics will have a limited dynamic range available to control the production of spatial forms and that more advanced stimulation methods may be required.